2019
DOI: 10.3390/cancers11050708
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Cannabinoid Type 1 (CB1) Receptor and its Downstream Signaling Pathways in Metastatic Colorectal Cancer

Abstract: Changes in the regulation of endocannabinoid production, together with an altered expression of their receptors are hallmarks of cancer, including colorectal cancer (CRC). Although several studies have been conducted to understand the biological role of the CB1 receptor in cancer, little is known about its involvement in the metastatic process of CRC. The aim of this study was to investigate the possible link between CB1 receptor expression and the presence of metastasis in patients with CRC, investigating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…It is therefore no surprise that there remains ambiguity in its precise role within cancer pathophysiology (Wu 2019 ). Many pre-clinical studies and histological analysis of patient tumours, suggest that an upregulation in the CB 1 and CB 2 receptors, endogenous ligands and over-activation of the ECS correlates with more aggressive tumours (Dariš et al 2019 ) although other reports have concluded the contrary (Jung et al 2013 ; Tutino et al 2019 ). Cancer is a heterogenous disease and current evidence should be interpreted on the basis that different tumour types have been shown to exhibit various levels of CB receptors as well as ECS components.…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore no surprise that there remains ambiguity in its precise role within cancer pathophysiology (Wu 2019 ). Many pre-clinical studies and histological analysis of patient tumours, suggest that an upregulation in the CB 1 and CB 2 receptors, endogenous ligands and over-activation of the ECS correlates with more aggressive tumours (Dariš et al 2019 ) although other reports have concluded the contrary (Jung et al 2013 ; Tutino et al 2019 ). Cancer is a heterogenous disease and current evidence should be interpreted on the basis that different tumour types have been shown to exhibit various levels of CB receptors as well as ECS components.…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, CB1 up-regulation was associated with a shorter survival time of CRC patients with stage II microsatellite-stable [32] or stage IV tumors [38]; whereas, CB2 receptor up-regulation in CRC tissue was correlated to higher proliferation levels and lymph node involvement, suggesting that also its expression could be a negative prognostic factor [34]. Conversely, in hepatocarcinoma high levels of both receptors have been associated with better disease-free survival rates [39,40]. Despite the reported evidence, the altered expression of CB receptors in several GI cancers is not strictly related to a straightforward cause and effect and must be further investigated.…”
Section: Gastrointestinal Cancersmentioning
confidence: 91%
“…The expression of CB2R is a poor prognostic factor in CRC and its activation via the AKT/GSK3β signalling pathway has been linked with a more aggressive phenotype [62]. On the other side, the down-regulation of CB1R has been linked with metastatic CRC [63]. Endogenous and synthetic cannabinoids elicit the suppression of CRC cells proliferation and migration and stimulate apoptosis, via receptor-dependent and independent mechanisms [64].…”
Section: Gastrointestinal Malignanciesmentioning
confidence: 99%